1980
DOI: 10.1152/ajpcell.1980.239.3.c66
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of calcium transport and binding by rat myometrium plasma membrane subfractions

Abstract: A gradient has been designed to yield two subfractions of plasma membrane vesicles from rat myometrium, a low buoyant density (8-24% sucrose) fraction N1 richer in 5'-nucleotidase and a higher buoyant density (24-30% sucrose) fraction N2, instead of a previously described fraction F1. Both N1 and N2 had very low activities of NADPH-cytochrome c reductase and succinate-cytochrome c reductase. Electron micrographs of thin sections of N1 showed clear vesicles, whereas N2 consisted of vesicles with electron-dense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

1981
1981
2001
2001

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 10 publications
4
10
0
Order By: Relevance
“…Although a heterogenous microsomal fraction was used in this study , the biochemical (Hurwitz et al, 1973;Kwan & Ramlal, 1982) and (c) most smooth muscles have sparse content of endoplasmic reticulum (Devine et al, 1972) and the distribution of ATP supported Ca2+ uptake parallels that of plasma membrane markers in isolated subcellular membrane fractions from various types of smooth muscles (Janis et al, 1977;Grover et al, 1980;Kwan et al, 1981) including stomach smooth muscles (Sakai et al, 1981;Kawn et al, 1982). Our present study shows that PLC is a useful tool for study of the functional role of membrane phospholipids in membrane associated enzymes and ion transport systems and the results are consistent with our previous report that PLC treatment causes smooth muscle cell membrane damage leading to inhibition of smooth muscle activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a heterogenous microsomal fraction was used in this study , the biochemical (Hurwitz et al, 1973;Kwan & Ramlal, 1982) and (c) most smooth muscles have sparse content of endoplasmic reticulum (Devine et al, 1972) and the distribution of ATP supported Ca2+ uptake parallels that of plasma membrane markers in isolated subcellular membrane fractions from various types of smooth muscles (Janis et al, 1977;Grover et al, 1980;Kwan et al, 1981) including stomach smooth muscles (Sakai et al, 1981;Kawn et al, 1982). Our present study shows that PLC is a useful tool for study of the functional role of membrane phospholipids in membrane associated enzymes and ion transport systems and the results are consistent with our previous report that PLC treatment causes smooth muscle cell membrane damage leading to inhibition of smooth muscle activity.…”
Section: Discussionmentioning
confidence: 99%
“…Such Ca2+ transport systems have been reported to be associated with isolated crude microsomal fractions (Carsten & Miller , 1977;Wuytack et al, 1978) or highly purified plasma membrane fractions (Grover et al, 1980;Kwan et al, 1981;Sakai et al, 1981). It is known that phospholipase C (PLC) inhibits action potential, simultaneously depolarizing resting membrane potential; and affects the ionic permeability of neuron and muscle cell membrane (Tobias, 1958;Albuquerque & Thesleff, 1967;Sakai, 1980) .…”
Section: Introductionmentioning
confidence: 99%
“…A23187, as a Ca2+ionophore [Pressman, 1976;Rosen berger and Triggle, 1978] prevents energydependent Ca2+ transport by destroying the Ca2+ concentration gradient across the mem brane vesicles and has no effect on Ca2+ bind ing [Kwan et al, 1979a, Scarpa et al, 1972, Inorganic phosphate, which forms precipitat ing complex with Ca2+ inside the membrane vesicles, enhances active Ca2+ transport [Godfraind 1 1 al., 1976;Batra, 1978;Kutsky and Goodman, 1978]. Hypotonic shock, when applied to the closed membrane vesi cles pre-loaded with Ca2+ causes swelling and bursting of membrane vesicles, and thus re lease of free Ca2+ being transported [Grover et al, 1980], Since we have not compared the sidedness of these types of vesicles, we must admit the possibility that our results could be explained by a lower proportion of insideout, non-leaking plasma membrane.…”
Section: Comparison O F Biochemical Propertiesmentioning
confidence: 96%
“…Inorganic phosphate or oxalate has com monly been employed to enhance the Ca2+ transport by isolated membrane fractions in the presence of ATP [Batra, 1978;Sulahke et al, 1973;Grover et al, 1980]. From pilot experiments we found that low concentra tions of oxalate (5-10 mM) had little effect on Ca2+ accumulation, while high concentra-TIM E, min tions of oxalate (50-100 mM) variably en hanced the Ca2+ accumulation by venous and arterial plasma membrane fractions (F,) not only in the presence and absence of ATP, but also the accumulation of Ca2+ on the Millipore filter in the absence of membrane frac tions.…”
Section: Effect O F Inorganic Phosphate On Calcium Accumulationmentioning
confidence: 99%
“…Restoration of cal cium concentrations compatible with relax ation therefore necessitates either the pump ing out or intracellular sequestration of this cation. Although a role has been proposed for mitochondria [4], and to a greater extent, for endoplasmic reticulum [3,32] in smooth muscle calcium regulation, recent studies have suggested a significant role for plasma membrane in calcium regulation [5][6][7][8][9], Stud ies involving plasma membrane-enriched vesicles from smooth muscle have in fact demonstrated the presence of an ATP-depcndent calcium pump with calcium transport properties favorable for the maintenance of such large gradients [7,8], Additional mechanisms may also exist for the regulation of free myoplasmic calcium. In particular, recent work strongly suggests the involvement of cyclic AMP-dependent pro tein kinases [10][11][12][13] and the calcium-depen dent regulatory protein calmodulin [14,15].…”
Section: Introductionmentioning
confidence: 99%